blue cheese mutations define a novel, conserved gene involved in progressive neural degeneration. - Finley, K.D.; Edeen, P.T.; Cumming, R.C.; Mardahl-Dumesnil, M.D.; Taylor, B.J.; Rodriguez, M.H.; Hwang, C.E.; Benedetti, M.; McKeown, M. (Journal of Neuroscience, 2003)
A common feature of many human neurodegenerative diseases is the accumulation of insoluble ubiquitin-containing protein aggregates in the CNS. Although Drosophila has been helpful in understanding several human neurodegenerative disorders, a loss-of-function mutation has not been identified that leads to insoluble CNS protein aggregates. The study of Drosophila mutations may identify unique components that are associated with human degenerative diseases. The Drosophila blue cheese (bchs) gene defines such a novel degenerative pathway. bchs mutants have a reduced adult life span with the age-dependent formation of protein aggregates throughout the neuropil of the CNS. These inclusions contain insoluble ubiquitinated proteins and amyloid precursor-like protein. Progressive loss of CNS size and morphology along with extensive neuronal apoptosis occurs in aged bchs mutants. BCHS protein is widely expressed in the cytoplasm of CNS neurons and is present over the entire length of axonal projections. BCHS is nearly 3500 amino acids in size, with the last 1000 amino acids consisting of three functional protein motifs implicated in vesicle transport and protein processing. This region along with previously unidentified proteins encoded in the human, mouse, and nematode genomes shows striking homology along the full length of the BCHS protein. The high degree of conservation between Drosophila and human bchs suggests that study of the functional pathway of BCHS and associated mutant phenotype may provide useful insights into human neurodegenerative disorders.